(untitled) (mathematica didactica, 2023)
The individual case study focuses on the interpretations and conceptual development of a child who is counting while solving a number problem, partially drawing on her stored basic knowledge. The child’s number concepts, notions on operations and strategic means were developed based on a concept designed to foster “Zahlenblick”. We analyzed the child’s developmental process throughout 13 learning units with an interpretative approach. We aimed understand the child’s development of strategic means and her ability to recognize and use the task’s characteristics, number patterns and numerical relationships. Two main characteristics seem to be central for the child’s ability to use relationships when solving problems.